DESIGN AND MANUFACTURE OF INDONESIAN NAVAL WARSHIP TECHNICAL CONDITION REPORT AND INVENTORY INFORMATION SYSTEM - Zainal Syahlan; Endro Prasetijoadi; Fatkulil Aswar Mahia; Adi Bandono (JOURNAL ASRO, 2018)
Information system is a system within an organization that meets the needs of processing dailytransactions, supports operations, is managerial and strategic activities of an organization and providescertain external parties with reports needed in inventory management which includes managing data inand out, data borrowers of goods and data including the condition of defense equipment that is stillsuitable for use or damaged conditions still use journal books and still rely on Microsoft office. Based onthe above problems, it is necessary to design and manufacture an inventory information system andreport technical conditions in the KRI environment that can assist in the creation, implementation anddevelopment of an inventory information system, avoiding errors in storing data files of goods, the personin charge of the inventory can quickly present data on the condition and readiness of the ship as materialfor reports for the head of the department to the commander and facilitate reporting and newcommander's policies and reporting to the unit. The technical condition report is an official regulation inorder to carry out routine technical reports of all levels at the KRI level with the aim of reporting the ship'sreadiness both inventory reports and ship material reports as routine technical instructions carried out bythe top command level ranks in order to prepare all ships preparedness for assignment military and nonmilitary.Keywords: Inventory Information System, Technical Condition Report.